Prophylactic effect of the traditional Chinese medicine formula danxiong granules (TDX105) on hand–foot skin reaction associated with the antitumor targeted drug regorafenib: a randomized, double-blind, placebo-controlled trial - Yu, Shuang; Hu, Xinrui; Tan, Yaqin; Wang, Caixia; Shao, Zhenyu; Xiao, Ying; Liu, Hailong; Lv, Jing; Li, Sheng; Jiang, Xuan; Zeng, Lingzhi; Tian, Aiping (Frontiers in Pharmacology, 2025)
BackgroundHand–foot skin reaction (HFSR) is the most common side effect of the antineoplastic drug Regorafenib. It severely affects patients’ quality of life, and no clear treatment is currently available for the condition. In preliminary clinical studies, the traditional Chinese medicine compound Danxiong Granules (TDX105) has shown significant therapeutic benefit for HFSR. This study aimed to evaluate the prophylactic effect of TDX105 for HFSR.MethodsA total of 137 colorectal cancer patients scheduled for Regorafenib treatment were randomly assigned in a 2:1 ratio to a treatment group (n = 91) and a control group (n = 46), which received basic treatment (topical urea ointment) plus TDX105 or placebo, respectively, for 8 weeks. Follow-up was conducted until tumor regression or Regorafenib discontinuation. The primary study endpoint was the incidence of HFSR within 8 weeks.ResultsThe total incidence of HFSR was markedly lower in the treatment group than in the control group (76.1% vs. 53.8%), particularly for grade 3 HFSR (7.7% vs. 19.6%, p = 0.041; absolute risk difference: 11.87%, 95% confidence interval: −0.01–0.25). Moreover, TDX105 significantly delayed the median onset time of HFSR (25 vs. 11 days, p < 0.001) and decreased the durations of grades 2 and 3 HFSR (grade 2: 12 vs. 22 days; grade 3: 5 vs. 13 days, p < 0.01). The rate of Regorafenib dose reduction due to HFSR was significantly lower in the treatment group (1.10% vs. 19.57%, p < 0.05). Importantly, the HFSR continuation rate was 0% in the treatment group, compared to 10.87% in the control group. Although tumor control rates were similar in both groups, progression-free survival was significantly improved in the treatment group (3.2 vs. 2.5 months, p = 0.048).ConclusionTDX105 significantly reduced the incidence and severity of Regorafenib-induced HFSR. This finding lends support to the use of TDX105 for prevention of HFSR.Clinical trial registrationNCT05289726.